1996
DOI: 10.1042/bj3150041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-3-3 proteins in human platelets: effects of synthetic peptides on protein kinase C activation

Abstract: The 14-3-3 proteins inhibit protein kinase C (PKC) activity in vitro and contain conserved sequences that resemble the pseudosubstrate domain of PKC and the C-terminus of the annexins. In the present study we have identified the isoforms of 14-3-3 in human platelets and used synthetic peptides derived from the regions with similarity to PKC and annexins to examine the potential role of 14-3-3 in regulating platelet activity. Immunoblotting studies with isoform-specific antisera raised against the acetylated pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…14-3-3 binding to several signal transducers (7-10) including PKC isotypes (18,41,42) has been reported, but controversial data exist as to the functional role of these interactions (7,8,41). Of relevance to the findings reported here, 14-3-3 has been described to inhibit PKC regulated interleukin-2 expression in T cells by preventing its translocation to the membrane (18).…”
Section: Discussionsupporting
confidence: 49%
“…14-3-3 binding to several signal transducers (7-10) including PKC isotypes (18,41,42) has been reported, but controversial data exist as to the functional role of these interactions (7,8,41). Of relevance to the findings reported here, 14-3-3 has been described to inhibit PKC regulated interleukin-2 expression in T cells by preventing its translocation to the membrane (18).…”
Section: Discussionsupporting
confidence: 49%
“…Many investigators have reported that 14-3-3s act as potential regulators of PKC, which is controlled by the interactions between them [10][11][12][13]. However, the effects of 14-3-3 on PKC have been controversial, showing conflicting results of inhibition or activation [5,9,13], and the biological significance of this event remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this isotype is present in significant amounts in the retina, as well as in the brain, and is necessary for light adaptation processes or differentiation in photoreceptors [7,8]. It is well established that 14-3-3 proteins function as a protein kinase C (PKC) regulator [9][10][11][12][13]. In vitro, 14-3-3 ζ has been reported to be an endogenous PKC inhibitor [5,14], but the role of 14-3-3 ζ in the diabetic retina remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets contain high levels of the , ␤, and ␥ isoforms and lower levels of the ⑀ and isoforms of 14-3-3 (2). The only isoform that has been shown to interact with GP Ib␣ is 14-3-3.…”
mentioning
confidence: 99%
“…Cas , BAD, and phosphatidylinositol 3-kinase (1)(2)(3)(4)(5), proteins such as Cdc25 and Wee1 that are involved in cell cycle control (6,7), and proteins such as FKHRLl and DAF-16 (8,9) that are involved in regulation of transcription.…”
mentioning
confidence: 99%